Characterizing the Interactions Among a Dinoflagellate, Flagellate and Bacteria in the Phycosphere of Alexandrium tamarense (Dinophyta) - Hu, Lidan; Peng, Xingyue; Zhou, Jingyan; Zhang, Yanmei; Xu, Shanghui; Mao, Xiaomei; Gao, Yahui; Liang, Junrong (Frontiers in Marine Science, 2015)
A small flagellate alga was isolated from the phycosphere of a toxic red tide dinoflagellate Alexandrium tamarense. Phylogenetic analysis and ultrastructural observations demonstrated that the small flagellate alga is a species belong to Ochrophyte Ochromonas sp. The process of ingesting bacteria by Ochromonas sp. was recorded by a time lapse capture under a light microscope. Through the use of different assemblages in the co-culture experiment, the species interactions in this phycosphere microenvironment were analyzed. We demonstrated that the growth of Ochromonas sp. was supported by bacteria. Three strains of bacteria ingested by Ochromonas sp. were isolated and identified to belong to α-, δ- and γ-Proteobacteria. The growth of A. tamarense was suppressed when co-cultured with bacteria. In contrast, Ochromonas sp. triggered the growth of A. tamarense by inhibiting the growth of algicidal bacteria. This result firstly demonstrated a positive effect of a flagellate on a dinoflagellate in the phycosphere of A. tamarense. Combined with other negative effects between dinoflagellates and bacteria or bacteria and flagellates, this study showed a series of clear interactions among dinoflagellate, bacterium, and flagellate in the dinoflagellate microenvironment.